Testing of a new high voltage electrical discharge generator prototype at high frequencies to assist anthocyanin extraction from blueberries. (December 2022) - Díaz-Álvarez, R.; Carullo, D.; Pataro, G.; Ferrari, G.; Segura-Ponce, L.
Abstract: Traditional extraction methods are based on high-temperature maceration with organic solvents, which are dangerous for human health. A viable alternative to overcome the issues associated with conventional extraction is to increase cell tissue permeability by applying high voltage electrical discharge (HVED) treatments. The objective of this work was to validate the electroporation of blueberry plant cells using a new HVED generator prototype at a high frequency, investigate the effect, intensity, and duration of the applied voltage, and recover anthocyanins from its electroporated cells. The electroporation level of the HVED-treated blueberries was measured qualitatively by transmission electron microscopy (TEM) analysis. Meanwhile, it was quantitatively measured by the cell permeabilization index (Zp) and anthocyanin extraction level. Results of the micrographs (TEM) showed electroporation in all treatments in which Zp was 0.24 when applying a 2 kV treatment for 2 s, whereas a 3-fold increase in tissue damage was revealed with the most powerful treatment (10 kV voltage, 30 s). In addition, anthocyanin values ranged from 83.09 ± 1.20 (control) to 136.82 ± 0.84 (HVED), which was 64.66% higher. The HVED treatment can increase mass transfer rates during conventional extraction processes. It should be noted that the validated prototype required a low specific energy requirement (31–204 kJ/kg) for proper tissue electropermeabilization. In conclusion, we demonstrated the capability of the developed HVED prototype to boost mass transfer phenomena and thus potentially increase its adaptability to assist dissimilar industrial processes or waste (e.g., peels and seeds) such as freeze-drying operations. Graphical abstract: Image 1 Highlights: A new high voltage electric discharge (HVED) prototype was developed. The parameters of the HVED prototype were validated. The HVED treatments were compared with traditional treatments. The HVED is a "green" method to extract valuable compounds from blueberries.